2005
DOI: 10.1016/j.neuron.2005.08.010
|View full text |Cite
|
Sign up to set email alerts
|

LIM Kinase1 Controls Synaptic Stability Downstream of the Type II BMP Receptor

Abstract: Here, we demonstrate that the BMP receptor Wishful Thinking (Wit) is required for synapse stabilization. In the absence of BMP signaling, synapse disassembly and retraction ensue. Remarkably, downstream Smad-mediated signaling cannot fully account for the stabilizing activity of the BMP receptor. We identify LIM Kinase1 (DLIMK1)-dependent signaling as a second, parallel pathway that confers the added synapse-stabilizing activity of the BMP receptor. We show that DLIMK1 binds a region of the Wit receptor that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
198
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(202 citation statements)
references
References 65 publications
4
198
0
Order By: Relevance
“…2C). This lag time suggests that BMP signaling operates through a change on the transcriptional level, whereas an effect through LIM kinase-mediated local cytoskeletal stability seems less likely (18,19). Indeed, DM did not cause an acute collapse of growth cones; rather, a depletion of pSmad1 in nuclei was observed (Fig.…”
Section: Smad1 Is Developmentally Regulated In Drg Neurons and Governsmentioning
confidence: 94%
See 1 more Smart Citation
“…2C). This lag time suggests that BMP signaling operates through a change on the transcriptional level, whereas an effect through LIM kinase-mediated local cytoskeletal stability seems less likely (18,19). Indeed, DM did not cause an acute collapse of growth cones; rather, a depletion of pSmad1 in nuclei was observed (Fig.…”
Section: Smad1 Is Developmentally Regulated In Drg Neurons and Governsmentioning
confidence: 94%
“…Indeed, noncanonical BMP signaling pathways have been implicated in mediating local effects of BMPs-regulating actin dynamics in dendritogenesis (19), acute growth cone collapse (33), and synaptic stability (18).…”
Section: Sensory Axon Regeneration By Activation Of the Bmp Pathway In Amentioning
confidence: 99%
“…While the overwhelming evidence indicates that all Wit responses in motoneurons are mediated through Smads, it is also possible that some non-canonical pathways contribute to BMP neuronal signaling (Baines, 2004;Eaton and Davis, 2005;Sun et al, 2007). To the extent that these Smadindependent pathways operate through transcriptional regulation (Lee et al, 2007), their targets would also have been identified in this screen.…”
Section: Cg13565 Encodes a Putative Neuromodulator Regulated By Bmp Smentioning
confidence: 99%
“…Growth and differentiation of Drosophila neuromuscular junctions (NMJs) require the retrograde BMP signal, named Glass bottom boat (Gbb), which is secreted from postsynaptic muscles and activates presynaptic BMP signaling (5). Transduction of BMP signaling via phosphorylation and transcription in motorneurons stabilizes transient synaptic structure, leading to overall synaptic growth (6). Whereas it is well recognized that activity-induced up-regulation of retrograde signals potentiate synaptic properties, conceptually it is also possible that parallel retrograde signals playing negative roles in synaptic properties are down-regulated by synaptic activity.…”
mentioning
confidence: 99%